Pengaruh Penyuluhan Baby Spa Terhadap Tingkat Pengetahuan Ibu di Posyandu - Nevia, Ike Elis; Umar, Marezza Yolanda; Sulistiawati, Yuni; Komalasari, Komalasari (Wellness And Healthy Magazine, 2021)
Baby Spa is a body treatment for babies that can be done in two ways, namely bathing or swimming and baby massage. One of the factors that influence the attitude of the mother in doing baby spa is knowledge. The benefits of a baby spa can increase appetite. The research objective was to see the effect of baby spa counselling on the level of knowledge of mothers at the community health service of Trikarya village, Penawartama sub-district, TulangBawang Regency. This type of research is quantitative research with experimental methods and research design “one group pre-test post-test design”. The population in this research were all mothers of children under five at the community health service of Trikarya village, who had children aged 0-18 months. The sampling technique used total sampling with samples at was 25 respondings. The bivariate analysis used a non-parametric test, namely the Wilcoxon test. The results showed that before being given counselling on good knowledge categories there were five respondents (20%) while after being given counselling on knowledge the higher 21 respondents (84%). The bivariate test results obtained a p-value less than 0.05, which means that there is effective counselling on the level of knowledge. In conclusion, there was an effect of baby spa counselling toward maternal knowledge levels in community health service of Trikarya village, Penawartama sub-district, TulangBawang Regency.